Pre- and Post-COVID-19 Antimicrobial Resistance Pattern of Pathogens in an Intensive Care Unit - Andreea-Loredana Golli; Ovidiu Mircea Zlatian; Monica Laura Cara; Mădălina Olteanu (MDPI AG, 2024)
We aimed to determine the trend of the antimicrobial resistance pattern of pathogens isolated in samples collected from patients hospitalized in the intensive care unit (ICU) in selected periods before and after COVID-19. A retrospective study of bacterial pathogens was performed on 1267 patients. Positive bacterial culture data from 1695 samples from the pre-COVID-19 period and 1562 samples from the post-COVID-19 period were obtained. The most frequently isolated bacteria in both periods were Staphylococcus aureus and Klebsiella spp. The resistance rates of Klebsiella spp. Significantly increased against colistin (0.38% to 20.51%), gentamicin (44.62% to 64.85%), and aztreonam (56.35% to 3.60%). There was a significant increase in the resistance rate against colistin for E. coli strains (4.69% to 32.46%) and for Acinetobacter sp. strains (3.37% to 18.09%). More than 50% of the Staphylococcus aureus strains were MRSA, with statistically significant increases in the antimicrobial resistance rate against doxycycline (40.08% to 51.72%), linezolid (0.22% to 3.13%), rifampicin (53.16% to 64.93%), and teicoplanin (26.31% to 53.40%). The study revealed a significantly increasing trend in the antimicrobial resistance rate of Gram-negative pathogens against certain antibiotics, including those used only in cases where there are no other therapeutic options.